5 - GATS and Higher Education in Nigeria: A Preliminary Investigation of the Indicative Patterns of Consumption Abroad by Nigerians - Olanrewaju Olaniyan,; Abiodun S. Bankole,; Olugboyega A. Oyeranti, (Journal of Higher Education in Africa, 2010)
This article presents some preliminary evidence on the existence and magnitude of consumption abroad and the type of trade in higher education, using a combination of advertisement survey data by Nigerians during 2001-2006 and secondary data on Nigerians enrolled in universities outside the coun- try. We found that higher education consumption abroad is increasing with- out explicit regulation by Nigeria’s regulatory bodies. The findings also point to the development of a market for local recruiting agencies and the need for regulation not only for quality control but also to avoid collusion between local students recruiting agencies, foreign higher education providers and foreign embassies. The study therefore proposes the setting up of a techni- cal committee to advise on issues concerning negotiations on higher educa- tion during the WTO rounds and also provide a clear framework on the process and dynamics of the trade for the benefit of the citizens and the country.